GEOLOGY OF THE BERTAM VALLEY TO POS BETAU FOCUSING ON GEOMECHANICAL PROPERTIES OF ANDESITE - PUA, MING JIA (Universiti Teknologi PETRONAS, 2015)
This paper reviews the first geomechanical analysis exposed along Bertam Valley to Pos Betau. It aims to construct a geological map of the transect, validate observed geological features in the field with published geology of Peninsular Malaysia, to describe the structural features of andesite and relate them to the regional structural history of Bentong-Raub suture and to delineate the geomechanical properties of andesite and relate them to fractured basement. The geological analysis suggest that our area of study are part of suture zone where serpentinite and ribbon bedded chert are observed in the field. These feature shows a part of an ophiolite package which are important in identifying paleo-ocean. While for the structural analysis, a major compressional force acted on the NNW-SSE direction indicates the major force involve during the tectonic evolution of Peninsular Malaysia which closely related to the closing of Paleo-Tethys Ocean and collision between Indochina and Sibumasu. For the geomechanical analysis, the unconfined compressive strength (UCS) that we obtain through lab testing shows similar trend in andesite rock strength. Beside the results from 3 different test (point load testing, uniaxial compressive strength test and triaxial compressive strength test) are correlatable among each other, showing high rock strength value. An initial prediction is made to relate the rock with fractured basement reservoir in Anding Field which are Permo-Carboniferous in age and have a closed fractured system trending NW-SE.